1984
DOI: 10.1002/joc.3370040506
|View full text |Cite
|
Sign up to set email alerts
|

The Southern Oscillation and its relation to the monsoon rainfall

Abstract: The interannual fluctuations in the Southern Oscillation indices (Wright, 1975) and their relations to the Indian monsoon (June-September) rainfall have been examined for the period of 106 years from 1875 to 1980. The monsoon rainfall is significantly (99.9 per cent level) correlated with the Southern Oscillation indices for the seasons: MJJ (069), A S 0 (0.67), NDJ (0.53), and FMA of the following year (0.38). The fluctuations in the Southern Oscillation index for the A S 0 season appear strongly related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…Shukla and Paolino (1983) also noted that the anomalous summer monsoon precedes the extreme phase of ENSO in autumn through winter. In other words, the two factors, i.e., the ENSO indices (SOI or SST in the equatorial Pacific) and the snow cover over Eurasia and Tibet, which are highly or moderately correlated with the Indian summer monsoon rainfall (Pant and Parthasarathy, 1981;Bhalme and Jadhav, 1984;Hahn and Shukla, 1976;Dickson, 1984 etc. ) should be inferred as parts of one climate system of global ENSO rather than independent external parameters.…”
Section: B Process Over Eurasia and Indian Oceanmentioning
confidence: 99%
“…Shukla and Paolino (1983) also noted that the anomalous summer monsoon precedes the extreme phase of ENSO in autumn through winter. In other words, the two factors, i.e., the ENSO indices (SOI or SST in the equatorial Pacific) and the snow cover over Eurasia and Tibet, which are highly or moderately correlated with the Indian summer monsoon rainfall (Pant and Parthasarathy, 1981;Bhalme and Jadhav, 1984;Hahn and Shukla, 1976;Dickson, 1984 etc. ) should be inferred as parts of one climate system of global ENSO rather than independent external parameters.…”
Section: B Process Over Eurasia and Indian Oceanmentioning
confidence: 99%
“…As an illustration, it must be emphasized that the IMR time series is not basically biennial as it is often assumed, but rather exhibits a triennial oscillation as many monsoon indicators (Bhalme and Jadhav, 1984). Recently, Fasullo (2004) has also questioned the existence of a biennial component in ISM variability.…”
Section: Introductionmentioning
confidence: 99%
“…The ENSO-monsoon teleconnections involve significant simultaneous relationships between monsoon rainfall and various ENSO indices (Krishna Kumar et al, 1995). It has generally been observed that negative southern oscillation index (SOI) (Bhalme and Jadhav, 1984;Parthasarathy and Pant, 1985) and warmer sea-surface temperature (SST) in the central and eastern equatorial Pacific are associated with lower monsoon rainfall and drought conditions (Angell, 1981;Khandekar and Neralla, 1984;Parthasarathy et al, 1988b;De, 1999), reducing crop production over India.…”
Section: Introductionmentioning
confidence: 99%